Improvement of power quality of power system using contingency analysis - C. Ramachandran, M; Elango, K (International Journal of Engineering and Technology, 2018)
Contingency analysis is a widely known feature in present day Energy Management System (EMS).The purpose of this strength gadget evaluation feature is to offer the operator records approximately the static security. Contingency analysis of electricity gadget is a major pastime in power device planning and operation. In fashionable an outage of any person of transmission line or transformer might also result in over hundreds in other branches and/or unexpected machine voltage upward push or drop. Contingency evaluation is used to calculate violation. This paper shows the instance on IEEE-14 bus system which offers statistics of violation & remedial action to do away with violations. Exact studies had been completed to work out the contingency plans.Â Â